Vertical Fast Handoff Technique For Mobile IPv6 in Heterogeneous 4G Networks - Solouk, Vahid (2009)
Over the recent years, mobility in wireless communications has become a big interest of communication and network researches due to the rising demand on and expectations of wireless Internet access. However, since none of the existing wireless technologies can individually fulfill all the tasks arising from the Internet users’ demands, the integration or coexistence of different communication systems having different network characteristics is inevitable. This integration on the other hand, requires seamless inter-system mobility solutions. Every inter-system roaming which leads to vertical handoff requires proper interaction of both link and IP layers, since network point of attachment as well as the device interface are involved in handoff. Many investigations in standardization are being made to finally design and implement each of these communication layers. This thesis details out the whole research, which is done in two main components. As for the first component, a link layer mechanism with the notion of a selection algorithm based on weighted mean is primarily introduced for collecting link layer information and discovering the candidate access router. This mechanism is then used as handoff decision phase with an improved mobile-assisted handoff method as an extension of Fast Mobile IPv6 Handoff (FMIPv6) in vertical mode. The performance of the proposed methods is discussed using analysis and comparison of simulation results with wellknown methods in the field. The method has been shown to achieve performance improvements in terms of higher preference level of selection for various cases, and in terms of latency and packet loss, by 45% and 83% respectively, while maintaining comparatively lower buffer sizes. As the second component, a framework is proposed to incorporate an integration mode of cellular and wireless networks called semi tightly-coupled. This framework is further used to design and implement an end-to-end roaming solution as Vertical Fast Handoff (VFHO) for the integrated network. The performance of the proposed framework has been analyzed mathematically and through simulations which show the robustness of VFHO in terms of signaling cost, endto- end packet delivery cost, overall handoff latency, and packet loss based on various system variables. Under several simulations, the number of lost packets encountered by VFHO stayed as low as 20 packets when the arrival rate was a maximum of 50 packets per second, and did not exceed 10 packets in the case when packet sizes was at a maximum of 256 Bytes or when buffer size was set to 50 KB. Besides, the delay varied between 200 and 600 ms in cases when the Duplicate Address Detection (DAD) and wireless link delays reached up to 600 ms and 70 ms, respectively. In conclusion, the selection-based decision mechanism in vertical handoff such as VFHO, can be good for congestion control, and achieve long-term objectives such as load sharing.